Eternity in the ether : a Mormon media history - Feller, Gavin (Urbana : University of Illinois Press, 2023)
"Mass media and the Church of Jesus Christ of Latter-day Saints evolved alongside each other, and communications technology became a fundamental part of the Church's institutions and communities. Gavin Feller investigates the impact of radio, television, and the internet on Mormonism and what it tells us about new media's integration into American life. The Church wrestled with the promise of new media to help implement its vision of Zion. But it also had to contend with threat that media posed to the family and other important facets of the Latter-day Saint faith. Inevitably, media technologies forced the leadership and lay alike to reconsider organizational values and ethical commitments. As Feller shows, the conflicts they faced illuminate the fundamental forces of control and compromise that enmesh an emerging medium in American social and cultural life. Intriguing and original, Eternity in the Ether blends communications history with a religious perspective to examine the crossroads where mass media met Mormonism in the twentieth century"--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 05, 2023).
eBooks on EBSCOhost
Keywords: Mass media -- Religious aspects -- Church of Jesus Christ of Latter-day Saints; Médias -- Aspect religieux -- Église de Jésus-Christ des saints des derniers jours; SOCIAL SCIENCE / General; Mass media -- Religious aspects -- Church of Jesus Christ of Latter-day Saints; Electronic books